Impact Of Transfer Policies On Employee Benefits And Organizational Needs- A Study With Reference To It Indistry In Chennai - S. Saranya,Dr. M. Chandran (International Journal of Advanced Science and Technology, 2020)
The Present Research Paper Intended To Measure The Impact Of Transfer Policies Adapted By The It Companies On The Organizational Needs And Employee Benefits. There Are Two U Tomes Those Are Measured Empirically Using Primary Data Obtained From Employees Of Top Five It Companies. The Researcher In Fact Exploited Exploratory Factor Analysis, Confirmatory Factor Analysis, Linear Multiple Regression Analysis To Prove The Proposed Model. The Results Proved That That The Transfer Policies Benefit Both The Organizations And Employees. These Benefits Are Very Attractive And Useful For Employee’s Retention